Complex Pathophysiology of Acute Kidney Injury (AKI) in Aging: Epigenetic Regulation, Matrix Remodeling, and the Healing Effects of H2S - Shreyasi Gupta; Subhadeep Mandal; Kalyan Banerjee; Hebah Almarshood; Sathnur B. Pushpakumar; Utpal Sen (Biomolecules)
The kidney is an essential excretory organ that works as a filter of toxins and metabolic by-products of the human body and maintains osmotic pressure throughout life. The kidney undergoes several physiological, morphological, and structural changes with age. As life expectancy in humans increases, cell senescence in renal aging is a growing challenge. Identifying age-related kidney disorders and their cause is one of the contemporary public health challenges. While the structural abnormalities to the extracellular matrix (ECM) occur, in part, due to changes in MMPs, EMMPRIN, and Meprin-A, a variety of epigenetic modifiers, such as DNA methylation, histone alterations, changes in small non-coding RNA, and microRNA (miRNA) expressions are proven to play pivotal roles in renal pathology. An aged kidney is vulnerable to acute injury due to ischemia-reperfusion, toxic medications, altered matrix proteins, systemic hemodynamics, etc., non-coding RNA and miRNAs play an important role in renal homeostasis, and alterations of their expressions can be considered as a good marker for AKI. Other epigenetic changes, such as histone modifications and DNA methylation, are also evident in AKI pathophysiology. The endogenous production of gaseous molecule hydrogen sulfide (H2S) was documented in the early 1980s, but its ameliorative effects, especially on kidney injury, still need further research to understand its molecular mode of action in detail. H2S donors heal fibrotic kidney tissues, attenuate oxidative stress, apoptosis, inflammation, and GFR, and also modulate the renin–angiotensin–aldosterone system (RAAS). In this review, we discuss the complex pathophysiological interplay in AKI and its available treatments along with future perspectives. The basic role of H2S in the kidney has been summarized, and recent references and knowledge gaps are also addressed. Finally, the healing effects of H2S in AKI are described with special emphasis on epigenetic regulation and matrix remodeling.